1997
DOI: 10.1016/s0304-3959(97)00010-9
|View full text |Cite
|
Sign up to set email alerts
|

Do patients with chronic pain selectively attend to pain-related information?: preliminary evidence for the mediating role of fear

Abstract: Preliminary evidence from a study using a modified Stroop paradigm suggests that individuals with chronic pain selectively attend to pain-related information. The current study was conducted in an attempt to replicate and extend this finding. Nineteen patients with chronic pain stemming from musculoskeletal injury and 22 healthy control subjects participated. All participants completed a computerised task designed to evaluate attentional allocation to cues thematically related to pain and injury via measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
108
2
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(128 citation statements)
references
References 23 publications
17
108
2
1
Order By: Relevance
“…Asmundson et al 40 44,45 . Also, the "Tampa scale for Kinesiophobia", the standard instrument to assess fear of (re)injury and movement, inadvertedly gave rise to the idea that the FA model is a model of phobia-based psychopathology in which patients hold "irrational and debilitating" beliefs 11 .…”
Section: Key Challenges To the Fa Model: We Are Not There Yetmentioning
confidence: 99%
“…Asmundson et al 40 44,45 . Also, the "Tampa scale for Kinesiophobia", the standard instrument to assess fear of (re)injury and movement, inadvertedly gave rise to the idea that the FA model is a model of phobia-based psychopathology in which patients hold "irrational and debilitating" beliefs 11 .…”
Section: Key Challenges To the Fa Model: We Are Not There Yetmentioning
confidence: 99%
“…Depression, pain-related fear, and catastrophizing are associated with increased interference, awareness of pain, and impaired disengagement from pain, and can moderate the effects of attentional coping leading to poor clinical outcomes. 11,19,23,35,47,87,103,123,152,179,195 Similarly, fear of injury or harm has an influence on physical effort and activity. 199 Given such data, it is recommended that psychosocial outcome measures also be administered when assessing physical functioning, as changes, or the lack of changes, in physical functioning following an intervention may be accounted for by existing fear, catastrophizing, and depression.…”
Section: Considerations Regarding the Use Of Physical Functioning Meamentioning
confidence: 99%
“…Still other research suggests that anxiety sensitivity plays a crucial role in a person in pain's bias to pain related information, a process crucial in the formation of enmeshment (Asmundson, Kuperos, & Norton, 1997). Based on the findings of the present study combined with previous research, anxiety sensitivity seems to playa moderating role between chronic pain and process variables in the A voidance Cycle such as anxiety, experiential avoidance, and enmeshment which in turn have a more direct effect on functional status.…”
Section: H5: Anxiety Sensitivity Will Moderate the Relationship Betwesupporting
confidence: 70%
“…The mutual maintenance model (Sharp & Harvey, 2001) argues that anxiety sensitivity is a vulnerability for catastrophizing, placing it in the first stage of the Avoidance Cycle. Asmundson, Kuperos, and Norton (1997) found that anxiety sensitivity had the largest effect on attention bias to pain related information, implying more importance in the Entanglement stage. Still other fear-avoidance based models have shown anxiety sensitivity as having direct and indirect effects on fear of pain and avoidance of pain-related stimuli (Norton & Asmundson, 2003;2004), placing anxiety sensitivity in stages one and three of the Avoidance Cycle, respectively.…”
Section: Predisposing Factors Towards the Avoidance Cyclementioning
confidence: 92%